Hubungan Dukungan Keluarga Dengan Kepatuhan Diet Pada Penderita Diabetes Melitus Tipe 2 Di Puskesmas Medan Sunggal 2024 - Handayani, Irma; Siregar, Ilham Syahputra; Siregar, Putri Awdes (Universitas Prima Indonesia, 2024)
Diabetes mellitus is a chronic metabolic disorder caused by blood sugar levels exceeding normal limits, namely temporary blood sugar levels equal to or more than 200 mg/dl and fasting blood sugar levels above or equal to 126 mg/dl. Type 2 diabetes mellitus is the most common type. Type 2 Diabetes Mellitus occurs due to progressive damage to the pancreatic β cells which causes the body to be unable to produce insulin and rejects the effects of insulin which is needed as an energy source for the body. One of the complications of diabetes mellitus is a decrease in bone density. The aim of this study was to determine the relationship between family support and dietary compliance in type 2 diabetes mellitus patients at the Medan Sunggal Community Health Center. This research uses quantitative research methods with a correlational design and a cross-sectional research design. The research population was all Type 2 Diabetes Mellitus clients at the Medan Sunggal Community Health Center and samples taken were 23 Type 2 Diabetes Mellitus sufferers taken using the Accidental sampling technique. The independent variable of the research is family support, the dependent variable is adherence to the Type 2 Diabetes Mellitus diet. The results of the study show that there is a significant relationship between family support and diet adherence. It is known that the correlation coefficient is 0.450, which means that the level of strength of the correlation/relationship is that the relationship is quite strong. It is hoped that the community health center will increase education for families to provide support to Diabetes Mellitus 2 sufferers about adhering to the Diabetes Mellitus diet. Key words: Family support, diet compliance, Type 2 diabetes mellitus